Varistor-like current-voltage characteristic of porous silicon - Vakulenko, O.V.; Kondratenko, S.V.; Shutov, B.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
The porous silicon (PS) current-voltage characteristic (CVC) has measured in transverse and longitudinal applied electric field. The obtained CVC has a varistor-like shape. Besides the practical application this confirms the PS grain structure whose influence is discussed in analizing the mechanism of the visible luminescence in PS.